Approximation results toward nearest neighbor heuristic - Monnot, J. (Yugoslav Journal of Operations Research; Vol 12 No 1 (2002): Vol. 12 No. 1, 2016)
In this paper, we revisit the famous heuristic called nearest neighbor (NN) for the traveling salesman problem under maximization and minimization goal. We deal with variants where the edge costs belong to interval [a